Powder Metallurgy - Fundamentals and Case Studies 2017
DOI: 10.5772/66872
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing, Composition, Properties and Application of Sintered Hard Metals

Abstract: Among other materials, hard metals represent an important family of functional materials. They show properties that are combinations of those of their constituents. The general idea while using hard metals is to exploit their excellent properties in terms of hardness, toughness, wear resistance, and chemical stability. These characteristics made hard metals as promising candidate for use as a cutting tool, which constitutes their main area of application. Depending on the particular use, the most important pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
4
0
4
Order By: Relevance
“…Technological developments have created the need for coatings that meet demanding applications of advanced materials. Single layer and multilayer coatings, widely used especially on cutting tools [1][2][3], increase the quality of machined parts and enable high speed cutting [1]. Titanium carbonitride (TiCN) coating is characterized by high hardness and low friction, can be applied by physical deposition (PVD) at temperatures ranging from 300 to 450°C [3], exhibits high melting temperature [4], anti-wear behaviour, chemical stability and corrosion resistance [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Technological developments have created the need for coatings that meet demanding applications of advanced materials. Single layer and multilayer coatings, widely used especially on cutting tools [1][2][3], increase the quality of machined parts and enable high speed cutting [1]. Titanium carbonitride (TiCN) coating is characterized by high hardness and low friction, can be applied by physical deposition (PVD) at temperatures ranging from 300 to 450°C [3], exhibits high melting temperature [4], anti-wear behaviour, chemical stability and corrosion resistance [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The costs of tungsten carbide (WC) production from primary tungsten are 4 times higher than those of WC recycled from scrap, according to international estimates. It can be clearly concluded that the recycling process is not only economically justified, but very desirable, especially in those areas where powder metallurgy has primate [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…O desempenho das ferramentas de HSS pode ser aumentado ainda mais pela aplicação de revestimento. Entre os revestimentos mais usados estão o nitreto de titânio, o qual permite aumentar a velocidade de corte e uma maior vida útil da ferramenta (HOSSEINI; KISHAWY, 2014;KLOCKE, 2011;TRENT;WRIGHT, 2000;PETER;ROSSO, 2017).…”
Section: Ferramentas De Corteunclassified
“…Devido a sua reduzida moabilidade e ao desenvolvimento de carbonetos sinterizados, o uso de Stellite ficou desatualizado rapidamente. A tendência progressiva no desenvolvimento de ferramentas de corte mais avançadas e duráveis continuou com a introdução do metal-duro ao longo da década de 1920 e com pastilhas de cerâmica após a Segunda Guerra Mundial (HOSSEINI; KISHAWY, 2014;KLOCKE, 2011;PETER;ROSSO, 2017).…”
Section: Ferramentas De Corteunclassified
See 1 more Smart Citation